2020
DOI: 10.1186/s12905-020-01065-8
|View full text |Cite
|
Sign up to set email alerts
|

Bridging different realities - a qualitative study on patients’ experiences of preoperative care for benign hysterectomy and opportunistic salpingectomy in Sweden

Abstract: Background Hysterectomy is a common procedure worldwide and removing healthy fallopian tubes at the time of hysterectomy (opportunistic salpingectomy) to possibly prevent ovarian cancer is increasing in frequency, but still controversial. The experiences and perceptions of women, eligible for the procedure, have not been previously investigated. This study aims to, among women waiting to undergo hysterectomy, explore i) experiences and perceptions of self and healthcare in relation to their elective surgery, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…In 2015, Kang et al surveyed 100 healthy volunteers to assess barriers to performing salpingectomy; 71% of respondents did not realize the seriousness of ovarian cancer, 79% were unaware of the theory that the fallopian tube is the origin of epithelial ovarian cancer, and 87% had never heard of salpingectomy as a preventive method for ovarian cancer. A 2020 study by Collins et al found varying patient opinions of salpingectomy, and the decision to undergo salpingectomy at the time of hysterectomy was perceived to be dependent on the counseling gynecologist. Similar findings were demonstrated by Gelderblom et al in 2021; the main barriers to implementing salpingectomy were lack of knowledge about the existence of the procedure (45%) and concerns about the removal of healthy organs (46%).…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Kang et al surveyed 100 healthy volunteers to assess barriers to performing salpingectomy; 71% of respondents did not realize the seriousness of ovarian cancer, 79% were unaware of the theory that the fallopian tube is the origin of epithelial ovarian cancer, and 87% had never heard of salpingectomy as a preventive method for ovarian cancer. A 2020 study by Collins et al found varying patient opinions of salpingectomy, and the decision to undergo salpingectomy at the time of hysterectomy was perceived to be dependent on the counseling gynecologist. Similar findings were demonstrated by Gelderblom et al in 2021; the main barriers to implementing salpingectomy were lack of knowledge about the existence of the procedure (45%) and concerns about the removal of healthy organs (46%).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to recognize and adequately attend the needs of women during the perioperative hysterectomy period, an aspect which has been evidenced by multiple studies, which report how insufficient is the information women have and how few opportunities they have to participate in this process, being reduced to depend on the health worker (6,28) .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we expect results from the qualitative stage to allow showing the meaning of education in the perioperative stage; questions and uncertainties regarding the surgical act and the state of health of women; as well as get closer to the experiences of women in the perioperative stages of hysterectomy and, therefore, from a professional perspective, to be able to understand this phenomenon and identify areas where an educational intervention can be carried out (28) , in order to contribute to the design and elaboration of the nursing educational intervention with the support of a webpage. Later, the quantitative results will allow us to know the effect of the educational intervention, as reported in intervention studies based on counseling, individualized recommendations for recovery based on experts, and education based on specific models, improving the variables mentioned before (12,(13)(14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of common definition to differentiate functional intestinal problems from postoperative paralysis, 16 and the patient's description of the grade of discomfort might be the deciding factor if it is regarded as a complication. In a study with women waiting for gynecological surgery in Sweden the women described insufficient knowledge of what to expect in the recovery after surgery 17 and an association between presurgical expectations and quality of life after surgery has been found. 18 The preoperative information that the woman receives most likely affects what symptoms she accepts to be a part of normal recovery and how she experiences them.…”
Section: Discussionmentioning
confidence: 99%